Comparative antibacterial activities and chemical composition of some plants' oils against Salmonella enteritidis - Dikbas, N.; Bagci, Eyup; Kotan, Recep; Cakmakci, Ramazan; Ozer, Hakan; Mete, Ebru; Erdogan, Guelsuem (Gaurav Soc Agricultural Research Information Centre-Aric, 2010)
It is known that many plant essential oils have been shown to possess antimicrobial activity. The aim of this study was to investigate the comparative antibacterial activities of the essential oils from seven different plant species collected from Turkey and two pure compounds against S. enteritidis at 25 degrees and 35 degrees C to determine the major compounds of the tested oils, and to test for sensitivity of S. enteritidis to a total of 12 antibiotics. Antibacterial activity assays were carried out by disc diffusion method with a minor modification. The main compounds of tested oils were analyzed by capillary GC and GC-MS. The results showed that all tested essential oils, pure compounds and 10 antibiotics showed antibacterial activity against pathogen. The oil of Satureja hortensis showed the strongest antibacterial activity, and its antibacterial activity was much stronger than that of seven antibiotics tested. GC and GC-MS results showed that carvacrol and thymol were the major compounds in all tested plant species. Consequently, this study indicated that especially the essential oils of Satureja hortensis, Origanum rotundifolium and Melissa officinalis had a potential to be used for medical purposes and as a food preservative.
Keywords: Antibacterial; essential oil; food preservatives; Melissa; Origanum; Salmonella; Satureja; Thymus